2005
DOI: 10.3171/foc.2005.18.5.13
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent or refractory trigeminal neuralgia after microvascular decompression, radiofrequency ablation, or radiosurgery

Abstract: Object Trigeminal neuralgia (TN) is characterized by paroxysmal lancinating pain in the trigeminal nerve distribution. When TN is refractory to medical management, patients are referred for microvascular decompression (MVD), radiofrequency ablation, or radiosurgery. After the initial treatment, patients may have refractory or recurrent symptoms requiring retreatment. The purpose of this study was to determine what factors are associated with the need for retreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 15 publications
1
36
0
2
Order By: Relevance
“…Several studies have indicated that patients with a history of prior surgical treatment failure are less likely to respond to GKRS than those who receive primary GKRS treatment (6-7, 9, 17). Despite this widespread use of salvage GKRS, little is known about the outcome, complications, and prognostic factors in this patient population (18). We present the first study to provide an in-depth analysis of GKRS as a salvage treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have indicated that patients with a history of prior surgical treatment failure are less likely to respond to GKRS than those who receive primary GKRS treatment (6-7, 9, 17). Despite this widespread use of salvage GKRS, little is known about the outcome, complications, and prognostic factors in this patient population (18). We present the first study to provide an in-depth analysis of GKRS as a salvage treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, their population contained a number of patients who had pain recurrence due to technical deficiencies (e.g., wrong nerve decompressed). In another analysis of patients with surgically refractory TN, Sanchez-Mejia et al (18) found that MVD was able to rescue 4 of 6 (67%), GKRS was able to rescue 14 of 20 (74%), and thermal rhizotomy was able to rescue 5 of 6 (83%). (18) Approach to patient selection…”
Section: Surgical Treatments As Salvage Modalitiesmentioning
confidence: 96%
“…In minority of cases pain might be due to multiple sclerosis (MS) or nerve compression by tumors. 16 TGN due to compression by tumors is about 4% and most common tumors are trigeminal schwannomas, acoustic neuromas, dermoid and epidermoids. Two percent (2%) of patients with MS have TGN, where as 18% of patients with bilateral TGN have MS. 13 Diagnosis is usually made by classical history, however, cranial imaging like CT Scan /MRI is indicated to exclude other pathology such as tumors, vascular malformation, MS and other abnormalities of brain Stem.…”
mentioning
confidence: 99%
“…Other drugs which are being used alone or in combination of carbamazepine are amitryptilline, gabapentine, pregabapentin and baclofen. 16 If medical treatment fails or is not tolerated surgical interventions are available. Surgical interventions ranged from ablative therapy like percutaneous rhizotomy to MVD.…”
mentioning
confidence: 99%
“…Even methods for radiation therapy have been developed, and it is not rare to encounter patients who require reoperation. 5,15 However, the surgical complication rate increases and the surgical success rate decreases at reoperation. 12 Surgical difficulties, in the form of adhesions and prosthetic materials, are sometimes encountered when performing reoperation via the same route that was initially used.…”
mentioning
confidence: 99%